EFEK NEFROPROTEKTOR EKSTRAK TEMULAWAK (Curcuma xanthorrhiza roxb) TERHADAP KADAR KREATININ TIKUS (Rattus Norvegicus) YANG DIINDUKSI PARACETAMOL - Putri, Jilan Fandini; Rizkawati, Muflihah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Paracetamol is commonly used as an analgesic and antipyretic. The toxic doses of paracetamol-induced toxic effects such as renal tubular necrosis. Creatinine (Cr) is a biochemical function to assess kidney function. In Indonesia, ginger is one of the leading plants which has health benefits, as a hepatoprotector and nephroprotector because it contains curcumin and xanthorrhizol. This research was conducted to determine the effect of ginger extract on the creatinine levels of Wistar rats induced by paracetamol. The method used an experimental pre-post-test control group design. The research subjects divided into five groups consisting of 5 rats, K1 (negative control), K2 ( paracetamol 2 g/kgBW), P1, P2, and P3 given curcuma 800 mg/kgBW, 1.600 mg/kgBW, 3.200 mg/kgBW and a toxic dose of paracetamol of 2 g/kgBW on the last three days. The data was analyzed with the Paired T-test followed by a one-way ANOVA test to see differences between groups. The results showed a significant difference between the creatinine levels of Wistar rats before and after treatment (p=0.029). Administration of graded doses of ginger to the Wistar Rat group which was induced by paracetamol, showed a significant difference compared to the control group, between groups K2 and P1 (dose 800 mg/kgBB) with a p-value=0.031. Based on the results, it can be concluded that graded doses of Temulawak can minimize damage to the kidneys of Wistar Rats due to paracetamol induction as shown by the difference in creatinine levels in the 800 mg/kgBB treatment group compared to the control group.